2020
DOI: 10.1007/s11121-020-01178-4
|View full text |Cite|
|
Sign up to set email alerts
|

Different Approaches to Address Bullying in KiVa Schools: Adherence to Guidelines, Strategies Implemented, and Outcomes Obtained

Abstract: We examined the extent to which school personnel implementing the KiVa® antibullying program in Finland during 2009–2015 systematically employed the program-recommended approaches (confronting or non-confronting), used one or the other depending on the bullying case (case-specific approach), or used their own adaptation when talking to perpetrators of bullying, and whether they organized follow-up meetings after such discussions. In addition to investigating adherence to program guidelines, we tested how effec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
21
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3
1
1

Relationship

2
3

Authors

Journals

citations
Cited by 22 publications
(26 citation statements)
references
References 33 publications
3
21
0
Order By: Relevance
“…As expected, the students’ intention to stop bullying was on average equally high for those who saw the condemning or empathy-raising message. This finding is in line with previous studies that found no evidence that either the confronting or non-confronting approach was overall more effective than the other (Garandeau et al, 2014 b; Garandeau et al, 2016 ; Johander et al, 2021 ). However, as it was also hypothesized, the students’ intention to stop bullying was highest for those who saw the combined message.…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…As expected, the students’ intention to stop bullying was on average equally high for those who saw the condemning or empathy-raising message. This finding is in line with previous studies that found no evidence that either the confronting or non-confronting approach was overall more effective than the other (Garandeau et al, 2014 b; Garandeau et al, 2016 ; Johander et al, 2021 ). However, as it was also hypothesized, the students’ intention to stop bullying was highest for those who saw the combined message.…”
Section: Discussionsupporting
confidence: 92%
“…Knowing which intervention strategies work best and for which student is essential for them. The few studies that have examined the relative effectiveness of different targeted anti-bullying interventions in real-life settings (Garandeau et al, 2014 b; Garandeau et al, 2016 ; Johander et al, 2021 ) are limited in two important ways. First, despite providing instructions to teachers about how to respond to bullying situations, the extent to which teachers followed these instructions was not known and could not be controlled for in the studies.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Most interventions aim for sustained change in the desired direction. Of particular relevance for practice, it must be ruled out that interventions backfire once the program ends (generate changes in the direction opposite of what was intended, see e.g., Johander et al, 2020 ). Program sustainability in terms of changes between posttest and follow-up test were apparent for both aggressive behavior and victimization in the models with and without covariates.…”
Section: Discussionmentioning
confidence: 99%